Downstream of Aromatherapy Oil for Relaxation and Reduction of Tantrum Intensity in Children with Autism - Istiani, Istiani; Kumalasari, Linda; Fatonah, Sri; Shafa Yumna Salsabila, Nabila; Tasya Salsabilah, Farah; Wardhani, Sri (Lafadz Jaya Publisher, 2023)
Tantrums are characteristic of emotional outburst behavior in autism and cannot be eliminated or cured. One of the alternative treatments to calm autism tantrums is through the use of essential oils using ingredients that have good properties for people with autism. Cocoa beans contain polyphenol compounds, theobromine, flavanols, amino acids tryptophan have good properties for people with autism. The eugenol compound content of clove flowers has a very distinctive aroma and is useful as a stimulant, local anesthetic, antiemetic, antiseptic, and antispasmodic. The utilization of cocoa beans and cloves has the potential to be used as essential oils. This activity aims to produce aromatherapy oil from natural ingredients, namely cocoa beans and cloves, mapping product excellence, and marketing mapping. The production of aromatherapy oil is carried out by making cocoa bean and clove oil through soxhlet extraction and product testing. Product testing was carried out by pH test, organoleptic test, and GC-MS test. The results of the calculation of B/C> 0 and R/C> 1, so the aromatherapy oil business is feasible to continue and develop.